Gradasi Bahasa di Pulau Kenari: Sebuah Studi Leksikostatistik - Imelda Imelda (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2013)
Kenari island or Alor is one of the islands in Nusa Tenggara Timur that has diversity of languages and cultures. Some people of this island said that different village has different language. Also, most of the tribes claim that their languages are different from other local languages. This statement triggers the researcher’s eagerness to clarify the existence of languages in Alor. In this case, the researcher tried to find the truth of statement of Alor ethnic tribes about their language diversity through lexicostatistics. The isolects1 investigated were taken from six tribes, i.e., Abui, Adang, Hamap, Kabola, Mor, and Pura. According to the analysis of their isolects, it is found that there are three dialects and four languages. It is also found that those dialects and languages come from one language family. of all, the researcher tried to clarify that the objective analysis of linguistics could be rejected for the reason of ethnicity that is claimed by the ethnic tribe.